Needs Analysis for Chatbot-Based Final Project Administration: A Qualitative Study at STT Terpadu Nurul Fikri - Mentari, Laisa Nurin (Information Technology and Science (ITScience), 2025)
The administration of undergraduate theses involves multiple stakeholders, including final-year students, academic supervisors, heads and vice-heads of study programs, program staff, and BAAK staff. This process often faces various challenges such as delays in information delivery, errors in form filling, inconsistencies in document format, and numerous repetitive questions regarding procedures and requirements. This issue adds to the workload of administrative staff and has the potential to hinder the timely completion of students' final projects. This research aims to analyze the needs and challenges in final project administration and identify the potential use of chatbot technology as a technology-based solution. The approach used is descriptive qualitative thru interviews, observations, and document analysis involving final-year students, supervising lecturers, and administrative staff. The research results indicate that chatbots have the potential to improve administrative efficiency by providing quick and accurate access to procedural information, document templates, guides, schedules, and motivational support. Thus, chatbots can function as interactive assistants that reduce staff workload, minimize miscommunication, and support the successful completion of final projects at STT Terpadu. Nurul Fikri. The novelty of this research lies in its focus on the needs analysis stage before chatbot implementation, which is still rarely done in previous studies. This approach provides a more structured basis for designing contextual and effective chatbot-based administrative systems in higher education environments.